Shaking Table Test of Composite Seismic Isolation System with Linear Guides and Constant Springs for the Cultural Collection - LIU Shuang; JI Jinbao; WANG Shiyu; ZHANG Weiqi (工程科学与技术)
ObjectiveThis study addresses the issue of immature vertical and three-dimensional seismic isolation technologies both domestically and internationally. A composite seismic isolation device that integrates linear guides and constant-force springs is designed and developed. This device, intended for the seismic isolation of artifacts in museum display cases, aims to mitigate potential earthquake-induced damage to artifacts.MethodsFirstly, two models of museum display cabinets and cultural relics, both at the same scale, were created based on those of a specific museum. One of the cultural relic models within the display cabinet was outfitted with a composite seismic isolation device incorporating linear guides and constant-force springs. The linear guide rail seismic isolation device was positioned at the bottom of the display cabinet, while the vertical constant-force spring seismic isolation device was placed at the base of the cultural relics. In contrast, the other system lacks a seismic isolation device. Secondly, two sets of cultural relic display cabinet systems were tested on a shaking table. The dynamic characteristics of both the seismic isolation-equipped display cabinets and the non-seismic isolation display cabinets were examined using white noise with an amplitude of 0.1g. Then, seismic waves of varying intensities and from different locations were applied. The acceleration response of the shaking table, the surface of the seismic isolation device, the top surface of the display cabinet, and the displacement response of the linear guide's horizontal seismic isolation device were measured. Finally, the acceleration at the top of the isolated display cabinet was compared to that of the non-isolated display cabinet. The horizontal and vertical isolation rates were calculated, and the displacement response of the vibration isolator was analyzed.Results and DiscussionsThe effectiveness of the isolation device in reducing seismic acceleration was clearly observed by comparing the top acceleration of isolated display cabinets with non-isolated ones. When comparing typical acceleration responses, under the EI‒Centro wave (0.4g) effect, the peak acceleration response in the X direction at the top of the non-isolated display cabinet was 1.68g, and in the Y direction was 1.89g. In contrast, on the isolated device platform, the peak acceleration response in the X direction was only 0.35g, and in the Y direction was only 0.36g. These results indicated that the isolation device effectively mitigated seismic acceleration. Through calculations, it was evident that the isolation efficiency of the linear guide's horizontal isolation device increased with the magnitude of seismic activity, ranging from 65% to 90%. This demonstrated the device's capability to effectively isolate vibrations in all horizontal directions. The isolation efficiency of the constant-force spring vertical isolation device ranged from 30% to 40%. The lower isolation efficiency in the vertical direction compared to the horizontal direction can have been attributed to different reference accelerations: Vertical isolation efficiency employed the Z-axis acceleration of the platform as a reference, while horizontal isolation efficiency used the acceleration of the non-isolated display cabinet as a reference. In terms of absolute acceleration values, the acceleration of the vertical isolation device was similar to that of the non-isolated horizontal display cabinet, indicating that this vertical isolation device effectively isolated vibrations in the vertical direction. The relative displacement of the horizontal isolation device on the linear guide increased with the intensity of the earthquake. At a seismic intensity of 0.1g, the relative displacement ranged from 5.9 to 24.9 mm in the X direction and from 5.4 to 21.1 mm in the Y direction. For a seismic intensity of 0.1g, the relative displacement was minimal for the Wenchuan wave in both the X and Y directions and maximal for the artificial wave in both the X and Y directions. Under a seismic intensity of 0.2g, the relative displacement ranged from 12.4 to 66.4 mm in the X direction and from 12.3 to 62.9 mm in the Y direction. For a seismic intensity of 0.2g, the relative displacement was minimal for the Wenchuan wave in both the X and Y directions, maximal for the artificial wave in the X direction, and maximal for the EI‒Centro wave in the Y direction. Under a seismic intensity of 0.3g, the relative displacement in the X direction ranged from 20.6 to 108.0 mm, and in the Y direction from 18.9 to 118.0 mm. The relative displacement was minimal for the Wenchuan wave in both the X and Y directions, maximal for the artificial wave in the X direction, and maximal for the EI‒Centro wave in the Y direction. Under a seismic intensity of 0.4g, the range of relative displacements in the X direction was between 31.4 and 140.0 mm, while in the Y direction, it spanned from 33.8 to 146.0 mm. For a seismic intensity of 0.4g, the relative displacement was minimal for the Wenchuan wave in both the X and Y directions, maximal for the artificial wave in the X direction, and maximal for the EI‒Centro wave in the Y direction. In all scenarios, the displacement of the isolation device did not exceed the designed effective stroke of 200 mm, indicating the reasonableness of the effective stroke design for the isolation device.ConclusionsThe conclusion indicates that the three-dimensional composite isolation system, which comprises a linear guide and a constant force spring, demonstrates a favorable isolation effect. This system has the potential to enhance the seismic safety of cultural relics during earthquake events. It exhibits strong innovation and practical applicability, fulfilling the three-dimensional isolation requirements of cultural relic display systems.